2010
DOI: 10.1002/ajmg.b.31018
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific association of the reelin gene with bipolar disorder

Abstract: The Reelin gene (RELN) encodes a secretory glycoprotein critical for brain development and synaptic plasticity. Post-mortem studies have shown lower Reelin protein levels in the brains of patients with schizophrenia and bipolar disorder (BP) compared with controls. In a recent genomewide association study of schizophrenia, the strongest association was found in a marker within RELN, although this association was seen only in women. In this study, we investigated whether genetic variation in RELN is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 36 publications
1
32
0
1
Order By: Relevance
“…It is tempting to speculate that PC loss in rl/+ mice is due to apoptosis, and that estradiol inhibits cell death by increasing reelin expression. Recent genetic studies have highlighted a link between variants of the reelin gene and risk of psychosis in women (Shifman et al, 2008;Goes et al, 2009). In conclusion, there is accumulating evidence that an interaction between altered reelin function and altered estrogen/ androgen balance could be an important pathophysiological mechanism in ASD, as well as other psychoses.…”
Section: Implications For the Neurobiology Of Asdmentioning
confidence: 99%
“…It is tempting to speculate that PC loss in rl/+ mice is due to apoptosis, and that estradiol inhibits cell death by increasing reelin expression. Recent genetic studies have highlighted a link between variants of the reelin gene and risk of psychosis in women (Shifman et al, 2008;Goes et al, 2009). In conclusion, there is accumulating evidence that an interaction between altered reelin function and altered estrogen/ androgen balance could be an important pathophysiological mechanism in ASD, as well as other psychoses.…”
Section: Implications For the Neurobiology Of Asdmentioning
confidence: 99%
“…Reelin (RELN) is a susceptibility gene for SCZ with genetic evidence from a GWAS using DNA pooling strategy [15] and several hypothesis-driven association studies across diverse populations [16][17][18][19], and variants in RELN have been reported to confer risk for BPD as well [20]. Recent studies have also demonstrated a reduction in RELN messenger RNA (mRNA) and protein expression in postmortem brain tissues of patients with SCZ and BPD [21,22], and other analyses indicated epigenetic aberrations of RELN in psychiatric disorders [23].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, rs362719 was found to be associated with a susceptibility to bipolar disorder in women but still may not be replicated (Goes et al, 2010). Since schizophrenia and bipolar disorder are closely related psychiatric disorders, it is encouraging to see a similar effect of rs362719 as regards the predisposition to schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the efforts to identify the cause of schizophrenia, it remains elusive as regards the definitive causes of the disorder. Another research has identified another variant (rs362719) of RELN gene, which has been found to increase the susceptibility to bipolar disorder patients in women (Goes et al, 2010). Based on the hypothesis that the overlap gene shares a similar background in both schizophrenia and bipolar disorder, we conducted a case-control study of this SNP locus (rs362719) to test the possible association with the schizophrenia in various Chinese populations.…”
mentioning
confidence: 99%